Fairness and effectiveness in policing : the evidence - Skogan, Wesley G.; Frydl, Kathleen (National Academies Press, 2004)
This book provides answers to the most basic question : What do police do? It reviews how police work is organized, explores the expanding responsibilities of police, examines the increasing diversity among police employees, and discusses the complex interactions between officers and citizens. It also addresses such topics as community policing, use of force, racial profiling, and evaluates the success of common police techniques. It goes on to look at the issue of legitimacy or how the public get information about police work, how police are viewed by different groups, and how police can gain community trust.